The Word of Mouth dalam Pembelian Kopi Keliling - Talitha Zaidah Azmi; Ratih Pandu Mustikasari (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2025)
Word of mouth, commonly known as reviews, has an important meaning for the success of a business. One of the businesses currently in high demand is food and beverage, especially coffee beverages. Over time, the coffee business has experienced many innovations, one of which is mobile coffee. The number of mobile coffee brands offered is not balanced with the number of purchases for each brand. So this intense competition makes consumers and potential consumers more selective in mobile coffee purchases. Word of mouth can push someone into the purchasing decision faster. This research aims to determine and test the extent of the influence of word of mouth on mobile coffee purchasing decisions in Surabaya. This research used explanatory research with a quantitative approach. Data was collected through a questionnaire distributed to 100 respondents based on predefined criteria. The results show a significant influence of word of mouth on mobile coffee purchasing decisions in Surabaya with a significance value of 0.430.